Urban agriculture in Portugal: availability of potentially toxic elements for plant uptake - Cruz, N.
Soils from urban areas often contain enhanced pseudo-total levels of potentially toxic elements (PTEs). Considering the expanding tendency of urban agricultural practices it is necessary to understand if these contaminants are available for plant uptake and if they pose risks to animal and human health. This study showed that estimates of Daily Intakes (DIs) of Cu, Pb and Zn for grazing animals were above animal Acceptable Daily Intakes (ADIs) at specific sites under the influence of an airport, an oil refinery and near highways with high traffic rates in the "Grande Porto" urban area (Portugal). These results suggest that there is a potential for dietary transfer of contaminants associated with the ingestion of both contaminated soil and feed by cows and sheep at unacceptably high concentrations.Furthermore, results showed that 40% of variability of ryegrass shoot contents of Cu, Pb and Ni; 60% for Ba; 70% for Zn; and 80% for Cd can be significantly (p<. 0.01) explained by the variability of the corresponding chemical available pools in soils. Since the chemical available pools of PTEs in urban soils were rather low when compared with the corresponding pseudo-total pools (median 0.1-5%) and even when compared with the corresponding reactive pools it is advised to perform further research on the conditions and time span for the limited availability of PTEs in urban soils, and to determine under which conditions PTEs on reactive forms may become available.